The Impact of Structural Inequities on Older Asian Americans During COVID-19 - Ma, Kris Pui Kwan; Bacong, Adrian Matias; Kwon, Simona C.; Yi, Stella S.; Ðoàn, Lan N. (Frontiers in Public Health, 2021)
Structural racism manifests as an historical and continued invisibility of Asian Americans, whose experiences of disparities and diverse needs are omitted in research, data, and policy. During the pandemic, this invisibility intersects with rising anti-Asian violence and other persistent structural inequities that contribute to higher COVID-19 mortality in older Asian Americans compared to non-Hispanic whites. This perspective describes how structural inequities in social determinants of health – namely immigration, language and telehealth access, and economic conditions–lead to increased COVID-19 mortality and barriers to care among older Asian Americans. Specifically, we discuss how the historically racialized immigration system has patterned older Asian immigrant subpopulations into working in frontline essential occupations with high COVID-19 exposure. The threat of ‘public charge’ rule has also prevented Asian immigrants from receiving eligible public assistance including COVID-19 testing and vaccination programs. We highlight the language diversity among older Asian Americans and how language access remains unaddressed in clinical and non-clinical services and creates barriers to routine and COVID-19 related care, particularly in geographic regions with small Asian American populations. We discuss the economic insecurity of older Asian immigrants and how co-residence in multigenerational homes has exposed them to greater risk of coronavirus transmission. Using an intersectionality-informed approach to address structural inequities, we recommend the disaggregation of racial/ethnic data, meaningful inclusion of older Asian Americans in research and policy, and equitable investment in community and multi-sectoral partnerships to improve health and wellbeing of older Asian Americans.